How Fintech Adoption, Digital Payment Systems, and Consumer Trust Shape Financial Performance of MSMEs - Nurchayati, Nurchayati; Ariyanti, Rini; Marianingsih, Ita (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the impact of fintech adoption, digital payment systems, and consumer trust on the financial performance of micro, small, and medium enterprises (MSMEs). Using data from 400 MSMEs, the research employs multiple regression analysis to explore the relationships between these factors. The results reveal that fintech adoption has the strongest positive influence on financial performance, followed by digital payment systems and consumer trust. Additionally, consumer trust moderates the relationship between digital payment systems and financial performance, highlighting the importance of customer confidence in driving business success. These findings emphasize the need for MSMEs to embrace digital financial solutions and build trust with their customers to improve their financial outcomes. The study provides practical implications for MSME owners, policymakers, and industry leaders, encouraging the adoption of fintech and digital payment systems as crucial tools for achieving competitive advantage and financial sustainability.